Representation of women in Malaysian literature in english - Nasirin Abdillah; Mazni Muslim; Nor Faridah Abdul Manaf (2010)
It is a fact that through the merging processes of multiculturalism and globalization, Malaysian's current community is fast changing. Malay women are among those who are undergoing transformations in which their religion and race continue to serve as tools in overcoming passions of recognition and marginalization so as to enable them mainstreaming their voices. the objectives of this paper is to investigate anad analyse the repsentation of women characters in contemporary Anglophone women's writing in Malaysia, focusing on predominant themes in creative prose fictions of three Malay Muslim writers - Che Husna Azhari, Dina Zaman and Ellina Abdul Majid. These three writers are not widely known;much less celebrated or studied in Malaysia, and knowledge about them is limited only to handful of people.This study is all the more important because of its being woefully under-researched.Moreover, there is rarely any focus on the contemporary Malay muslim women writers who are part of the legacy and continuation of the Malaysian Anglophone women literry tradition seeded in pre-Independence years and who now form a larger presence in contemporary literary scene in Malaysia. The method used in the study is based on islamic theoretical framework focusing mush on islamic principles found in the Quran, Prophetic Hadith and Sunnah and Muslim writers' scholarly writings.The data for this qualitative study is based on the writer's collection of short stories and novels - Che Husna Azhari's Melor in Perspective (1993); Dina Zaman's Night and Day(1997) and Elina Abdul Majid's Perhaps in Paradise (1997) and Khairunnisa : A Good Woman(1998). In addition, interviews with the writers are done in person to gain inside information. The findings of the writers' works in terms of the characterization of women,predominant themes and women-centred topics show that the writers are writing as women who are conscious of their female identify while depicting various potraits of women who faced all kinds of problems and heartaches in facing challenges in the dynamic changing of Malaysian's coming community. Islamic message and articulation show that islamic mores and values are still embedded in their writings. They are consciously aware of their identity as muslim writers exposure to Western education and years of living abroad.The implication of the study is to add to the body of critical studies on contemporary Anglophone women's writing in Malaysia as the selected writers are not widely known. Knowledge of them is limited to a certain group of audience. Future researchers should conduct more studies on other contemporary Malay Muslim women writers in areas of stylistic and aesthetic aspects of the writers.